Legality and Implications of International Law on Cooperation between Indonesia and Norway in the Environmental Sector - Loso Judijanto; Desi Asmaret; Agus Septima Ridwan; Bekti Utomo; Sahrul (Inovasi Pratama Internasional. Ltd, 2024)
The issue of environmental protection has become a significant concern in international relations, with numerous countries striving to preserve the environment through various initiatives. One such initiative is the conduct of international cooperation, which is implemented through a special program on the environment. This study seeks to ascertain the dynamics of the cooperation between Indonesia and Norway on environmental matters, with a particular focus on the Reducing Emissions from Deforestation and Forest Degradation (REDD+) programme, which operated from 2017 to 2021. The objective of this initiative, which falls under the umbrella of environmental cooperation, is the reduction of greenhouse gas emissions resulting from deforestation and forest degradation. The REDD+ program is a funding mechanism designed to support initiatives aimed at mitigating greenhouse gas emissions resulting from deforestation and forest degradation. The methodology employed in this research entails the utilization of qualitative research techniques, namely descriptive analysis, to generate insights from the data collected. This study's theoretical approach is informed by the context of international cooperation, particularly the historical bilateral relationship between Indonesia and Norway. The results of this research indicate the implementation of cooperation between Indonesia and Norway in the environmental sector through the REDD + program between the years 2017 and 2021, which was met with a number of significant challenges. These included issues related to the protection of forests, delays in fulfilling cooperation requirements, and disagreements with indigenous peoples. Additionally, the study identifies the problem of the implementation of Result Based Payments by Norway and the termination of Indonesia-Norway REDD+ cooperation.